The IMPLEMENTASI PEMBINAAN KEAGAMAAN DAN NILAI-NILAI KEARIFAN LOKAL MELALUI PEMBERDAYAAN MASYARAKAT DI KECAMATAN PUJANANTING - Syamhari; Ahmad Suryadi (PPM LP2M UIN Alauddin Makassar, 2021)
Implementation of religious development and local wisdom values ​​through community empowerment in Pujananting District. The purpose of this service is to provide assistance, empower the community in the implementation of religious development and the values ​​of local wisdom in Pujananting District. This community service was carried out for six weeks. The service team carried out the preparation of activities in the form of initial actions, namely preparing a community empowerment plan in the implementation of religious values ​​for six days by means of FGD (Focus Grouf Discussion). This community service activity has been successfully implemented and has received a very good response from the community. This is based on the fact that 73.3% of the 30 people sampled gave the opinion that community empowerment activities had an influence on the mastery of the religious field. Meanwhile, only 8 people or 26.7% stated that community empowerment had no effect on increasing religious knowledge obtained through community empowerment.